(untitled) (Journal of Plant Disease Sciences, 2023)
Okra [Abelmoschus esculentus (L.) Moench]is the only vegetable cropof significance in the Malvaceae family and isvery popular in the Indo-Pak subcontinent. In India, it ranks first in its consumption. The crop was found to suffer from stem and root rot disease in severe form in many region of Gujarat state during Kharif, 2021. So for its management different biocontrol agents evaluated under field condition, recorded minimum disease incidence 17.88 % was recorded in T. viride @ 2.5kg/ha +fluorescens @ 2.5kg/ha+ 300 kg FYMwhich was found at par with T. harzianum@ 2.5kg/ha+ P. fluorescens@ 2.5kg/ha + 300 kg FYM with 22.07 per cent disease incidence and the highest yield (100.99 q/ha) was obtained in T. viride @ 2.5kg/ha +P. fluorescens @ 2.5kg/ha+ 300 kg FYM, which was statically at par with T. harzianum@ 2.5kg/ha+ P. fluorescens@ 2.5kg/ha + 300 kg FYM(94.65 q/ha).